2011
DOI: 10.1007/s11664-011-1774-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of 4H-SiC JBS Diodes Fabricated with Tungsten Schottky Barrier

Abstract: Tungsten is a suitable metal contact for high-temperature applications. We fabricated 1.7-kV and 6-kV 4H-SiC junction barrier Schottky (JBS) diodes with a tungsten Schottky contact with different geometries, and their forward characteristics were measured up to 300°C. The 1.7-kV diodes exhibited unipolar conduction up to 6 V at 275°C, whereas 6-kV diodes showed ideal on-resistance, R on . An optimized JBS design permits a higher breakdown voltage to be obtained than for the pure Schottky diode, with a reasonab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…1 This has been attributed to the exceptional chemical, mechanical, and physical properties of the metal and the superior semiconductor and physical properties of SiC. In a comparative study of metal contacts on 4H-SiC, Gora et al 2 concluded that the W and 4H-SiC couple would be the most suitable for fabrication of devices that can operate at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This has been attributed to the exceptional chemical, mechanical, and physical properties of the metal and the superior semiconductor and physical properties of SiC. In a comparative study of metal contacts on 4H-SiC, Gora et al 2 concluded that the W and 4H-SiC couple would be the most suitable for fabrication of devices that can operate at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the W/ 4H-SiC junction has been shown to have remarkable junction properties and great potential in the implementation of high voltage microelectronic devices. 1,3 In miniature microelectronic devices, the influence of ultra-low contamination from formation of silicides and carbides on metal-semiconductor structures and interfaces becomes highly critical to device fabrication yield and determines their lifetime. 4 In silicon, it has been shown that tungsten contamination can be introduced during dopant implantation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to propose an analytical model for designing the device and optimizing the power of merit. At present, some analytical models for conventional SBDs have been presented [4][5][6][7], but for a FJ_SBD, researches were mainly based on numerical simulations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such test was submitted to two groups of 5 W-SBD's, the first one at room temperature (RT, 25°C), and the second one at 200°C. Since the aspect ratio between Schottky and bipolar contact is larger in SBD's [13], the effect of temperature on the current density balance can be better studied, while the results can be extensible to JBS structures at different current scales [14]. To perform such analysis, the infrared (IR) emission of the weak spots, acting as hot spots, was modulated and detected by using the Small sIgnal Modulation for Thermal Analysis (SIMTA) technique.…”
Section: Introductionmentioning
confidence: 99%
“…1 depicts the structure and some technological details of the tested diodes: the Schottky contact is formed by tungsten (W) deposition on top of a 12 lm-thick N-type SiC drift layer (5 Â 10 15 cm À3 doping concentration). The W-SBD's feature the same edge termination technology described in [13], which consist, as shown in Fig. 1(a), in a junction termination extension (JTE) and three floating guard rings (aluminum ÀAlÀ dose: 10 13 cm À2 ), and a field stopper with three assisting guard rings [16] in the JTE (200 nm deep, Al doping: 10 19 cm À3 ).…”
Section: Introductionmentioning
confidence: 99%